Cognitive-Postural Interference in Multiple Sclerosis - Chamard Witkowski, Ludivine; Mallet, Mathieu; Bélanger, Mathieu; Marrero, Alier; Handrigan, Grant (Frontiers in Neurology, 2019)
Multiple Sclerosis (MS) is a neurodegenerative disease associated with cognition and balance impairments, which can lead to accidental falls. Postural control requires cognitive resources. This interaction is quantifiable by using the dual-task paradigm. The cognitive-postural interference (CPI) is commonly evaluated through an assessment of the dual-task cost (DTC). However, heterogeneous methodology for the assessment of DTC creates ambiguity and complicates comparison of results documenting a CPI. The aim of this review was to summarise literature related to process, results and effects of CPI in MS patients. The Prisma statement was used to guide this systematic review. Eligible articles had to include participants with MS for whom CPI was assessed using the DTC. A total of 14 articles meeting inclusion criteria were retained. All studies used the double stance with eyes open for the postural task component. Three types of cognitive tasks were used: Stroop Color–Word Test, Word List Generation and the Backward Counting. However, cognitive task scores in single or dual task were unavailable in 11 studies, which prevented calculating the DTC for that task. Prioritization instructions were provided in seven studies. Mutual interference was shown in three studies, postural interference in nine and postural facilitation in two. This review highlights the presence of CPI among MS patients. Postural interference usually occurred during dual task while cognitive performance during dual task was rarely reported. The prioritization instructions seem to influence performance during the dual task, also task performance does not appear to vary based on EDSS level.